Pengaruh Size, Beta, Price To Book Value, dan Koneksi Politik Terhadap Return Saham pada Perusahaan yang tergabung dalam Indeks LQ-45 di Bursa Efek Indonesia Periode 2014-2019 - Finna Kurniasih; Lela Nurlaela Wati; Tati Rajati (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Valuation of company shares through fundamental analysis is a process carried out to estimate the price of shares in the future by estimating various fundamental factors that affect stock prices and linking the relationships between variables. This study aims to analyze the effect of Size, Beta, Price to Book Value, and Political Connections on stock returns in companies that have been listed on the LQ-45 Index in the 2014-2019 period. The method in this study is quantitative obtained from the company's financial statements that have been audited on the IDX during the 2014-2019 period. The sample in this study used a purposive sampling technique with a total of 67 companies. The data analysis technique used multiple linear regression analysis assisted by Eviews 10 software. The panel data regression model estimation technique was carried out using the Common Effects Model, Fixed Effects Model, and Random Effects Model approaches. The model specification test obtained the result that the most appropriate model was the Common Effect Model approach. Based on the results of data analysis shows that Size has a significant negative effect on stock returns. Beta has a positive or significant effect on stock returns. PBV has a significant negative effect on stock returns. Political connection has an insignificant negative effect on stock returns. It is hoped that this research can contribute positively to the development of theories about financial performance on stock returns, for investors who wish to invest their funds in securities, so that they can better consider Size, Beta, PBV, as a basic part in making a decision. This is because it can affect stock returns.